Le financement du régime de rentes du Québec - Faille, Jacques; Lévesque, Robert; Rousseau, Henri-Paul (L'Actualité économique, 1978)
The goal of this paper is to present an analysis of the problems raised by the financing of the Quebec Pension Plan. In the first step, we shall try to identify the reasons underlying the financing problem. In the second step, we shall deal with the various financing methods and their impact on the level, the structure and the rate of increase of the contributions to the Plan. Finally, we shall conclude on the financing method which, in our view, should prevail.